Proceedings of the 14th International Conference on Extending Database Technology 2011
DOI: 10.1145/1951365.1951399
|View full text |Cite
|
Sign up to set email alerts
|

Efficient execution plans for distributed skyline query processing

Abstract: In this paper, we study the generation of efficient execution plans for skyline query processing in large-scale distributed environments. In such a setting, each server stores autonomously a fraction of the data, thus all servers need to process the skyline query. An execution plan defines the order in which the individual skyline queries are processed on different servers, and influences the performance of query processing. Querying servers consecutively reduces the amount of transferred data and the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…SkyPlan was proposed in [36] for improving the performance of PaDSkyline [13]. Similar to PaDSkyline, during query processing, each peer reports a set of minimum bounding rectangles (MBRs) to the querying peer as a summarization of its data.…”
Section: Skyplan [36]mentioning
confidence: 99%
See 4 more Smart Citations
“…SkyPlan was proposed in [36] for improving the performance of PaDSkyline [13]. Similar to PaDSkyline, during query processing, each peer reports a set of minimum bounding rectangles (MBRs) to the querying peer as a summarization of its data.…”
Section: Skyplan [36]mentioning
confidence: 99%
“…On the other hand, AGiDS requires global knowledge of a grid structure with identical boundaries for all peers, which may not be feasible in some applications. Furthermore, in [36] it has been shown that SkyPlan outperforms PaDSkyline due to a more efficient execution plan. In case multiple hops are required for contacting each peer, the cost of these approaches increases since at most N p hops are required for gathering the summaries or querying the peers at each step leading to a cost of O(N p )+ O(N p ) (for AGiDS) or O(N p )+ O(2· N p ) (for PaDSkyline, SkyPlan).…”
Section: Unstructured P2p Systemsmentioning
confidence: 99%
See 3 more Smart Citations